2006
DOI: 10.1152/japplphysiol.01373.2005
|View full text |Cite
|
Sign up to set email alerts
|

Reports of the length dependence of fatigue are greatly exaggerated

Abstract: Relative force depression associated with muscle fatigue is reported to be greater when assessed at short vs. long muscle lengths. This appears to be due to a rightward shift in the force-length relationship. This rightward shift may be caused by stretch of in-series structures, making sarcomere lengths shorter at any given muscle length. Submaximal force-length relationships (twitch, double pulse, 50 Hz) were evaluated before and after repetitive contractions (50 Hz, 300 ms, 1/s) in an in situ preparation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 19 publications
2
18
0
Order By: Relevance
“…However, it has been shown that the apparent rightward shift in the force-length relationship is similar after isometric contractions and after eccentric contractions (9) and it has been suggested that this shift may be an artifact of the manner in which active force is calculated (10). Furthermore, it has been demonstrated that fascicle length is not affected by a series of fatiguing isometric contractions (11).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been shown that the apparent rightward shift in the force-length relationship is similar after isometric contractions and after eccentric contractions (9) and it has been suggested that this shift may be an artifact of the manner in which active force is calculated (10). Furthermore, it has been demonstrated that fascicle length is not affected by a series of fatiguing isometric contractions (11).…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylation of the light chains should also be greater with a higher number of stimulations, as this is a Ca 2+ dependent process. Fatigue and potentiation are also both length dependent [16,22], but in these experiments, potentiation clearly has the greater impact at short lengths.…”
Section: Interaction With Fatiguementioning
confidence: 62%
“…Fascicle lengths change half as much as whole muscle length [16] during passive length adjustments, so the range of lengths tested corresponds to RL±11% of fascicle length. Twitch, double-pulse, and 50 Hz (300 ms) contractions were recorded at each test length, similar to a previous study [19]. When testing lengths longer than RL, the muscle was held at the stretched length only long enough to obtain the contraction and was returned to RL for the rest period.…”
Section: Methodsmentioning
confidence: 99%
“…After 45 min, submaximal active force-length relationships for twitch, double-pulse, and 50-Hz contractions were recorded again in each series. This recovery period would be expected to permit metabolic recovery in the muscle, but low-frequency fatigue is known to persist [13,19]. Waiting for this period would permit evaluation of contractile amplitude at several lengths without detectable impact of continuing recovery affecting these measurements.…”
Section: Fatigue Experimentsmentioning
confidence: 99%
See 1 more Smart Citation